Communicating Shariah and Regulatory Frames for AI-Powered Halal Auditing - Aimi Aisyah Abu Bakar; Norhayati Rafida Abdul Rahim; Muhammad Nizam Awang (Universiti Sains Islam Malaysia, 2026)
Non-Indexed Publication